2015
DOI: 10.1021/acs.inorgchem.5b02236
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Metal Complexes of Bidentate Nitroxide Ligands: Synthesis and Electrochemistry

Abstract: We report rare earth metal complexes with tri- and bidentate ligands including strongly electron-donating nitroxide groups. The tridentate ligand 1,3,5-tris(2'-tert-butylhydroxylaminoaryl)benzene (H3arene-triNOx) was complexed to cerium(IV) in a 2:1 ligand-to-metal stoichiometry as Ce(Harene-triNOx)2 (1). Cyclic voltammetry of this compound showed stabilization of the tetravalent cerium cation with a Ce(IV/III) couple at E1/2 = -1.82 V versus Fc/Fc(+). On the basis of the uninvolvement of the third nitroxide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…While redox‐active ligands have been proven to impart interesting magnetic or electrochemical properties to the rare earth elements due to their ability to stabilize ligand radicals, fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al.…”
Section: Figurementioning
confidence: 99%
“…While redox‐active ligands have been proven to impart interesting magnetic or electrochemical properties to the rare earth elements due to their ability to stabilize ligand radicals, fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al.…”
Section: Figurementioning
confidence: 99%
“…While redox-active ligands have been proven to impart interesting magnetic [8,9] or electrochemical [10][11][12] properties to the rare earth elements due to their ability to stabilize ligand radicals, [13,14] fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al reported tetradentate Schiff base complexes of Nd, Eu, Tb,Ybthat, upon reduction, store two electrons in anew CÀC s bond.…”
mentioning
confidence: 99%
“…Ce(IV) alkoxides ( Table 7 ) have been applied as protonolysis reagents for the synthesis of Ce(IV) complexes, as demonstrated by Kim et al with the synthesis of 8-coordinate complex [Ce(Harene-TriNOx) 2 ] ( 213 , HareneTriNOx = {[(2- t BuNO)C 6 H 4 ] 2 [(2- t BuNOH)C 6 H 4 ]C 6 H 3 } 2– ) ( Scheme 63 ). 560 Gulino et al attempted to use Ce(O i Pr) 4 in salt elimination reactions with Tl(Cp) or Mg(Cp) 2 without success, observing reduction to Ce(III) instead. 561 Nonetheless, when the tin reagent R 3 SnCp (R = Me, n Bu) was employed, they were able to isolate Ce(Cp) 3 (O i Pr) ( 214 ), though structural authentication was not obtained ( Scheme 63 ).…”
Section: Oxygen Donorsmentioning
confidence: 99%